Sensitivity to Change of Objectively-Derived Measures of Sedentary Behavior - Chastin, S.; Winkler, E.; Eakin, E.; Gardiner, P.; Dunstan, D.; Owen, N.; Healy, Genevieve (Routledge, 2015)
The aim of this study was to examine the sensitivity to change of measures of sedentary behavior derived from body worn sensors in different intervention designs. Results from two intervention studies: Stand up for Your Health (pre-post home-based study with older adults not in paid employment) and Stand Up Comcare (non-randomized controlled trial in the workplace) were analyzed to quantify sensitivity to change of measures of total and accumulation of sedentary time obtained from hip-worn Actigraph and thigh-worn activPAL monitors. Sensitivity to change varied with intervention design and population considered. The activPAL was generally more sensitive but not consistently for all measures and designs. Measures of sedentary time accumulation, in particular half-life bout duration (W50%), were consistently more sensitive than total sedentary time. Measurement devices used in intervention studies need to be appropriately selected to be sensitive to changes in the behavioral target. For sedentary behavior interventions, measures of accumulation should be considered as outcomes.